2021
DOI: 10.3389/fvets.2021.742926
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Heat Exposure Among Pet Dogs in Rural and Urban Settings in the Southern United States

Abstract: With advancing global climate change, heat-related illnesses and injuries are anticipated to become more prevalent for humans and other species. Canine hyperthermia is already considered an important seasonal emergency. Studies have been performed on the risk factors for heat stroke in canine athletes and military working dogs; however there is limited knowledge on environmental risk factors for the average pet dog. This observational study explores variation in individually experienced environmental temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Heat stress experienced both during the day and at night contribute to heat-related mortality in humans [ 54 ], with heat-sensitive sub-populations (including the elderly and hospital patients) most likely to be located in areas with the highest night-time temperatures [ 40 ]. We echo the suggestion by Moon et al [ 51 ] that traditional measures of local temperature, such as heat index data from local weather stations, are likely to underestimate the risk of heat exposure for dogs. Further research aimed at predicting heat risk for dogs in different locations and housing types is needed.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Heat stress experienced both during the day and at night contribute to heat-related mortality in humans [ 54 ], with heat-sensitive sub-populations (including the elderly and hospital patients) most likely to be located in areas with the highest night-time temperatures [ 40 ]. We echo the suggestion by Moon et al [ 51 ] that traditional measures of local temperature, such as heat index data from local weather stations, are likely to underestimate the risk of heat exposure for dogs. Further research aimed at predicting heat risk for dogs in different locations and housing types is needed.…”
Section: Discussionsupporting
confidence: 84%
“…These data are therefore an estimation of the local environmental (shaded) conditions and are unlikely to fully represent the true conditions actually experienced by the dogs [ 40 ]. A recent US study compared ambient temperature data from thermometers mounted on dogs’ collars to neighbourhood and local weather station temperature records [ 51 ]. That study reported that the dog-mounted thermometers generally recorded lower ambient temperatures than the local weather station reported during the day for indoor housed dogs, but dogs housed outdoors in urban locations recorded higher local ambient temperatures than either the neighbourhood or regional weather stations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, performance in animals falls below its optimum during cooling and warming (15). Since extreme weather events, including thunderstorms, torrential rains, and flooding, are predicted to rise in frequency and severity (16), increased attention is necessary to identify and implement adaptation strategies (17). During last years, changes in temperatures and precipitation patterns have been evidenced in Italy, with events of extreme heat, torrential rains lasting for days and sudden and violent thunderstorms increasingly frequent (18), likely leading owners to change their routine based on the weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, only one study in English (26) has examined the potential environmental impacts related to a dog's entire life cycle. Few studies investigated the most common triggers of heat-related illness and injuries in dogs in the UK (7,17,27) and the environmental impacts of companion dog's and cat's food consumption (26). However, limited attention has been given to the environmental factors contributing to canine and feline behavioral changes.…”
Section: Introductionmentioning
confidence: 99%